Modeling of the Tensile Behavior FRCM Systems for Repair and Strengthening Interventions of Masonry Structures - Grande, Ernesto; Milani, Gabriele; Bertolesi, Elisa; Fagone, Mario; Rotunno, Tommaso (Frontiers in Built Environment, 2020)
Fiber Reinforced Cementitious Matrix (FRCM) systems are an innovative solution for strengthening interventions of existing masonry and concrete constructions. The current literature provides interesting experimental and numerical studies which underline the potentialities of FRCMs and their specific features. Direct tensile tests are generally used for characterizing the behavior of FRCM strengthening systems. These tests particularly underline the occurrence of both matrix cracking and debonding of the reinforcement from the matrix, phenomena which particularly influence the performance of FRCM systems. The present paper aims at numerically analyzing the response of FRCM strengthening systems during tensile tests carried out throughout different setup configurations. To this end, a simple model carried out from literature and opportunely modified is presented in the paper and validated with reference to experimental case studies. Moreover, the obtained results are critically examined to emphasize the role of the proposed model for the interpretation of the results carried out from standard tensile tests.